2007
DOI: 10.1111/j.1365-3083.2007.01930.x
|View full text |Cite
|
Sign up to set email alerts
|

Epitope Mapping of Series of Monoclonal Antibodies Against the Hepatocellular Carcinoma‐associated Antigen HAb18G/CD147

Abstract: The hepatocellular carcinoma‐associated antigen HAb18G/CD147, a member of CD147 family, could promote tumour invasion and metastasis via inducing the secretion of matrix metalloproteinases (MMP). Anti‐CD147 monoclonal antibodies (MoAb) have exhibited obvious inhibitory effect on MMP induction. However, none of the epitopes of these MoAb has been reported. We previously prepared five MoAb against HAb18G/CD147, named HAb18, 3B3, 1B3, 5A5 and 4D2. To map the epitopes of these MoAb, a series of truncated fragments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…The protein pellet was resuspended in cold acetone and the precipitation step was repeated. Samples were analyzed by immunoblotting with antibodies against extracellular CD147 (HAb18 antibody, prepared by our laboratory) [21] or intracellular CD147 (C-19 antibody, Santa Cruz Biotechnology, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The protein pellet was resuspended in cold acetone and the precipitation step was repeated. Samples were analyzed by immunoblotting with antibodies against extracellular CD147 (HAb18 antibody, prepared by our laboratory) [21] or intracellular CD147 (C-19 antibody, Santa Cruz Biotechnology, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…19 However, in contrast to these findings, another study found that the sequence AAGTVFTT-VEDLGSKILLTCSLNDSATEV (positions 22-50 in the human EMMRIN sequence), which does not include our epitope at all, was responsible for the EMMPRIN MMP induction activity and association with tumor invasion. 20 We suggest that because we used an antibody to target a specific epitope of 11 amino acids, we could use a shorter sequence than the two previous studies that used peptides to directly generate a steric hindrance or to compete with the homophilic binding to EMMPRIN. More importantly, all of these epitope-mapping studies focused only on the MMP-induction activity of EMMPRIN, and showed that it might span over a stretch of about 40 amino acids, but no data so far revealed the epitope responsible for the VEGF-induction activity of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…HAb18 is a monoclonal antibody (MAb) against the Ig-C2 domain (specific to basigin-2) (20). Recombinant protein B23ID-64P (IgI domain, consisting of 64 residues from T121 to C185 of basigin-2) and synthetic polypeptide B4N-11P (11 residues from the N terminus of basigin-4, MKQSDASPQER-C) were used as antigens for the preparation of rabbit polyclonal antibodies B23ID and B4N11, respectively, against the IgI domain (specific to both basigin-2 and basigin-3) and basigin-4.…”
Section: Methodsmentioning
confidence: 99%